Provider facility type and HPV vaccination rate among African American teenagers in the United States - Odo, Chinenye C.; Igbokwe, Mesoma A.; Odoh, Ikenna S.; Ndu, Ezinne A.; Agbo, Nneoma M.; Ugwunweze, Vivian C.; Okeke, Nzubechukwu G.; Okwu, Chiadikaobi A.; Chukwuma, Obinna V.; Okolie , Cynthia O. (International Journal Of Community Medicine And Public Health, 2023)
Background: The Human Papilloma Virus vaccine is one of the most efficient preventive vaccinations on the market to prevent HPV infection and has made significant advances in human vaccination. This study aimed to examine the relationship between the provider facility type and HPV vaccination rates, among African American teenagers. By exploring the potential relation of the two, we hope to inform programs and further studies into boosting HPV vaccination rates by targeted provider-based interventions. Methods: This cross-sectional study was conducted using data from the National Immunization Survey for Teen (NIS-TEEN) for the year 2021. This study focused on African American teenagers, aged 13 to 17 years, living in non-institutionalized households in the United States in 2021. Data was collected in two phases -the household interview phase and the provider data collection phase. Statistical analysis was conducted using weighted provider data, and all analysis was done using SAS Studio 3.81. Results: Provider facility type was significantly associated with HPV vaccination status (p≤0.0001). Specifically, respondents who used hospital facilities and public facilities had higher odds of having received at least one dose of the HPV vaccine when compared to those who used private facilities (OR=1.86; 95%CI; 1.84,1.89) and (OR=1.72; 95% CI; 1.70, 1.74) respectively. Conclusions: Results of this study suggest that provider facility type is associated with HPV vaccination status among African American teens in the US. There is however a need for definitive longitudinal studies to establish the relationship between provider type and HPV vaccination rates in African American teens.